Influence of Second-Year Students' Participation on Learning Outcomes at ICFP (Instituto Católico para a Formação de Professores) Baucau - Maria Sidalia de Oliveira, Edviges (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
Student participation in learning is an important aspect of their academic success. Therefore, this research aims to understand the influence of second-year students' participation in learning on study results at the Catholic Institute for Teacher Training (ICFP). ICFP conducted this research, which involved 61 second-year students, thereby qualifying it as population research. The researcher selected the research subjects using a random sampling technique. The research method used to collect data is quantitative, and the research instrument is a questionnaire survey. The questionnaire used a Likert scale measure. To assess that the instrument is valid, reliable, and normally distributed, the researcher tested it through validity, reliability, and normality tests. The researcher tested the validity of the questionnaire items using the 'empirical validity' technique, which involves correlation testing using SPSS21. The Cronbach alpha technique tests the reliability of credible items. The normality test of the instrument used ‘Kolmogorov-Smirnov.’ Linked to the data analysis technique, the researcher used simple linear regression to measure the influence between two variables. Thus, the research results indicated that student participation did not influence their study results. This finding indicates that other factors that may influence their learning outcomes include motivational, social, and learning quality factors.